Balancing acts: the role of TGF-β in the mucosal immune system - Konkel, Joanne E. (2011)
The gastrointestinal mucosal immune system faces unique challenges in dealing not only with fed antigens but also both commensal and pathogenic bacteria. It is tasked with digesting, transporting and using nutritional antigens whilst protecting the host from pathogenic organisms. As such, mechanisms that mediate effective immunity and immune tolerance are active within the gut environment. To accomplish this, the mucosal immune system has evolved sophisticated mechanisms that safeguard the integrity of the mucosal barrier. Transforming growth factor-β (TGF-β) emerges as a key mediator, balancing the tolerogenic and immunogenic forces at play in the gut. In this review we discuss the role of TGF-β in the generation and functioning of gut lymphocyte populations. We highlight recent findings, summarize controversies, outline remaining questions and provide our personal perspectives.